Population Size Does Not Predict Artifact Complexity: Analysis of Data from Tasmania, Arctic Hunter-Gatherers, and Oceania Fishing Groups - Read, Dwight (eScholarship, University of California, 2012)
A mathematical model purporting to demonstrate that the interaction population size of a group of social learners is a primary determinant of the level of technological complexity achieved by the members of that group through imitation of the most skilled individual in the group has been proposed. Empirical validation of the model has been attempted with archaeological data from Tasmanian hunter-gatherers and ethnographic fishing data from Oceania, but these data do not support the model. Data from a wide variety of hunter-gatherer groups show, instead, that implement complexity varies with an interaction effect between risk and number of annual moves and not with the interaction population size. Data from the Polar (Inuit) Eskimo and the Angmaksalik Inuit on the east coast of Greenland show that complex implements were part of both group’s technological repertoire even though each had interaction population sizes limited to a few hundred individuals, in direct contradiction with predictions from the mathematical model. The problem with the model lies in an invalid assumption.